Criminal records and public sector professional education: The role of criminal background checks in admissions to social work courses in England - Bald, Caroline; Wyllie, Aaron; Martinez Herrero, Maria Ines (Probation Journal, 2023)
Over 11 million people in England and Wales have criminal records, with men, people from Black, Asian and Minority Ethnic backgrounds and people from poorer communities being over-represented. A gatekeeping discussion is developing across the social work profession regarding the role of criminal records in decision-making at the point of admissions to social work programmes. Balancing risk, representation, and the right to move on, who becomes a social worker is an issue of debate among practitioners, educators, and policy makers, where notable instances of media and political focus on social work failure has led to public mistrust, and moral panic about the state of the profession. Whilst internationally many social work education providers have moved away from interview gatekeeping, in England this has continued, alongside wider checks including for criminal records. This discussion article reviews what social working with a criminal record represents in the profession and why course admissions is a site for restorative justice and the human right to move on.
Keywords: criminal records; inequalities; social work education; gatekeeping; human rights; Emerging; Scopus